English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

N = jane
M = jim

N = 3M + 6
N+14 + M+14 = 86 // substitute for N
3M + 6 + 14 + M + 14 = 86
4M + 34 = 86
4M = 52
M = 13
N = 3*13 + 6 = 45, Jane is 45

2007-02-20 02:53:53 · answer #1 · answered by TankAnswer 4 · 0 1

Jim's age = x
Jane's age = 3x +6
(14+x) +(14 + 3x +6) =86
34 +4x =86
4x =52
x = 13 therefor jane's age now is 13(3) +6 = 45

2007-02-20 11:25:14 · answer #2 · answered by bignose68 4 · 0 1

x=Jane
y=Jim

x=6+3y

In 14 yrs their ages will be,
Jane=x+14 //we know x=6+3y therefore substituting x = 6+3y+14= 20+3y
Jim=y+14

Their total age is 86
So,
20+3y+y+14=86
34+4y=86
4y=52
y=13

Therefore Jane's age now=86-Jim's age
= 86-(y+14)
= 86-(13+14)
= 86-27
= 59 yrs-final answer
------------------------------------------------------------------------------------

2007-02-20 11:09:25 · answer #3 · answered by roadrunner1335 2 · 0 1

fedest.com, questions and answers